New taxa and combinations in Neotropical Delphacini (Hemiptera: Fulgoroidea) - Lenicov, Ana M. Marino De Remes; Brentassi, M. Eugenia (Zootaxa, 2017)
A new South American genus of Delphacini (Hemiptera: Fulgoromorpha: Delphacidae), Neodelphax n. gen., is described. It includes a new species, N. sakakibarai sp. n., which is described herein, and two species that are removed from the genus Dicranotropis. All of them are illustrated. Supplementary descriptions of female N. fuscoterminata (Berg) comb. n. and N. acheron (Fennah) comb. n., including some new records and host plant associations are added. A preliminary key for males and females of South American species of Neodelphax with representative illustrations is also provided.